Роль Донецького ботанічного саду НАН України у вивченні й збереженні біорізноманітності степів південного сходу України - Glukhov, A.Z.; Ostapko, V.M.; Prikhod'ko, S.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2002)
The main areas of biodiversity research of the southeastern Ukraine steppes: floristic, critical-and-systematical, geobotanic, introduction, sozological have been characterized.